Balancing conditions of planar mechanisms with multi-degree of freedom - Khang, Nguyen Van; Dien, Nguyen Phong; Son, Pham Van (Vietnam Journal of Mechanics, 2005)
This paper presents a new method for deriving the balancing conditions of planar mechanisms with multi-degree of freedom. The method has advantage of being suitable for the application of the widely accessible computer algebra systems such as MAPLE. In the example, the conditions for complete shaking force and shaking moment balancing of a planar five-bar linkage are given.